PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PROBLEM POSING PADA SISWA KELAS V SD - Wiwik Elpina; Ikhsan Maulana Putra (Jurnal Muara Pendidikan, 2023)
This research started with the problem of teachers rarely asking questions, lack of activity in learning, students rarely asking opinions and students rarely asking questions in learning. This results in low student activity and learning outcomes. This research is classroom action research with a qualitative and quantitative approach. The research subjects were 35 class V students at SDN 105/II Rambah. In its implementation, this research consists of two cycles, each cycle consisting of planning activities, implementing actions accompanied by observation and reflection in each cycle. The results of this research can be seen from the students' visual, oral and mental activities. In cycle I the results of this research were focused on activities, namely (1) making experiments/questions (2) asking and answering questions (3) discussing (4) expressing opinions (5) solving problems, obtained an average in cycle I of 91%. Meanwhile, in cycle II, meeting I averaged 97.6% and meeting II 98%. This can also be seen in the completeness of student learning outcomes in cycle I, namely 20 students (57%) who completed, and 15 students (43%) who did not complete. Meanwhile, in cycle II student learning outcomes increased, namely 30 students (85%) who completed, and 5 students (15%) who did not complete. Based on the results of this research, it can be concluded that the Problem Posing model can improve student activity and learning outcomes in class V.